DETERMINAN PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG PERMANEN PADA WANITA USIA SUBUR DI PROVINSI JAWA TENGAH (ANALISIS DATA PENDATAAN KELUARGA 2024) - Charles Firmansyah Pasaribu (Jurnal Kesehatan Masyarakat, 2026)
Permanent Long-Term Contraceptive Methods (LTCMs) are prioritized in Indonesia’s Family Planning Program due to their effectiveness in reducing fertility rates and maternal mortality. However, data from the 2024 Family Data Collection show that only 19.7% of women of reproductive age (WRA) in Central Java use permanent LTCMs, while most prefer temporary methods such as IUDs (40.6%) and implants (39.7%). This study aimed to determine the prevalence and associated factors of permanent LTCM use among WRA in Central Java. An analytic observational study with a cross-sectional design was conducted using secondary data from BKKBN's 2024 survey. Bivariate analysis employed the Chi-Square test, and multivariate analysis used logistic regression. The results showed that several factors were significantly associated with permanent LTCM use, including age, age at first marriage, education, parity, ideal number of children, religion, knowledge of side effects, occupation, insurance ownership, access to services, and support from health workers (p < 0.001, except age at first marriage p = 0.060). Multivariate analysis revealed that WRA aged 40–49 were 12.8 times more likely to use permanent LTCMs than those aged 10–19 (AOR = 12.822). Women with parity >3 had 7.2 times higher likelihood (AOR = 7.299), while those with an ideal number of children >3 were less likely to use permanent LTCMs (AOR = 0.860). These findings emphasize the need to strengthen education, access, and support systems to increase permanent LTCM use.